Effects of dysprosium oxide addition in bismuth sodium titanate ceramics - Watcharapasorn A. (2014)
This research focuses on the preparation and characterization of dysprosium-doped bismuth sodium titanate (BNT) ceramics. The compounds were prepared using the conventional mixed-oxide method. The amount of dysprosium oxide used was varied from 0 to 2 at.%. The mixed powders were calcined at 800 °C and checked for phase purity using X-ray diffraction technique. The powders were then cold-pressed into small pellets which were subsequently sintered at 1050 °C for 2 h. The results from density measurement and SEM micrographs showed that highly dense and high-purity ceramics were obtained. The grain size of Dy-doped samples was found to decrease with increasing Dy content. Compared to pure BNT, the addition of Dy2O3 in BNT ceramics slightly increased the dielectric constant values near room temperature. In addition, the Dy doping resulted in a more diffused transition temperature, less frequency dependence of the dielectric constant and very low values of the dielectric loss. © 2007 Springer Science+Business Media, LLC.